2014
DOI: 10.3389/fonc.2014.00050
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Time Intervals between Pre-Operative Radiotherapy or Chemoradiotherapy and Surgery in Rectal Cancer?

Abstract: Background: In rectal cancer therapy, radiotherapy or chemoradiotherapy (RT/CRT) is extensively used pre-operatively to (i) decrease local recurrence risks, (ii) allow radical surgery in non-resectable tumors, and (iii) increase the chances of sphincter-saving surgery or (iv) organ-preservation. There is a growing interest among clinicians and scientists to prolong the interval from the RT/CRT to surgery to achieve maximal tumor regression and to diminish complications during surgery.Methods: The pros and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 97 publications
0
27
0
1
Order By: Relevance
“…In these cases pre-operative MR may not only direct surgical dissection, but also alert the MDT to the need for further upfront systemic chemotherapy, contact radiotherapy or extended surgical resection. In this cohort of patients, the identification of an optimal time for surgery post-NACRT which coincides with maximal oncological down-staging is an urgent question [21,31]. This pilot study suggests that further volume reduction and down-staging occurs between Week 9 and Week 14 post-NACRT, with more favourable ymrT, ymrTRG and volume changes found at Week 14.…”
Section: Interobserver Agreementmentioning
confidence: 82%
“…In these cases pre-operative MR may not only direct surgical dissection, but also alert the MDT to the need for further upfront systemic chemotherapy, contact radiotherapy or extended surgical resection. In this cohort of patients, the identification of an optimal time for surgery post-NACRT which coincides with maximal oncological down-staging is an urgent question [21,31]. This pilot study suggests that further volume reduction and down-staging occurs between Week 9 and Week 14 post-NACRT, with more favourable ymrT, ymrTRG and volume changes found at Week 14.…”
Section: Interobserver Agreementmentioning
confidence: 82%
“…Similarly, in a study conducted with 1593 patients attending 92 Dutch hospitals who underwent preoperative ccrt, the highest chance of pathologic complete response was noted when the interval between ccrt and surgery was about 11 weeks, with no apparent further increase being noted beyond that time 14 . Prolongation of the interval to 6-8 weeks or more from 4-6 weeks to improve rates of local control or survival has been considered not to be reasonable in tumours considered upfront to be resectable 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a higher degree of downsizing and downstaging 10e12 weeks after completion of CRT before surgery. 18,19 At the time of this study the general policy was to perform surgery after eight weeks. CK 20 is a well known stable biomarker for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%